2023
DOI: 10.1128/jvi.01366-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reinfection with SARS-CoV-2 Omicron Variants in Previously Infected Hamsters

Abstract: The emergence of SARS-CoV-2 variants and the widespread use of COVID-19 vaccines has resulted in individual differences in immune status against SARS-CoV-2. A decay in immunity over time and the emergence of variants that partially evade the immune response can also lead to reinfection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The Syrian golden hamster has become the preclinical animal model of choice to assess vaccine effectiveness against SARS-CoV-2 variants, as well as the likelihood of reinfections ( 16 , 21 28 ). Such information is critical for rational decisions around vaccine strain updates or other public health responses to the continuing emergence of new variants.…”
Section: Discussionmentioning
confidence: 99%
“…The Syrian golden hamster has become the preclinical animal model of choice to assess vaccine effectiveness against SARS-CoV-2 variants, as well as the likelihood of reinfections ( 16 , 21 28 ). Such information is critical for rational decisions around vaccine strain updates or other public health responses to the continuing emergence of new variants.…”
Section: Discussionmentioning
confidence: 99%
“…With human clinical data examining multiple exposures to coronaviruses 12,63,64,71,72 , including SARS-CoV-2 [73][74][75][76][77][78] , being inconsistent due to host factors and co-morbidities, it is essential to have the ability to study infection-reinfection in appropriate animal models for experimental variable isolation. Ferrets 79,80 , hamsters [81][82][83][84][85][86][87][88] , and non-human primates 89,90 , have all been used to study secondary challenge with SARS-CoV-2. While a primary exposure to the SARS-CoV-2 ancestral strain in rhesus macaques can lead to weight loss, viral load in respiratory and gastrointestinal tracts as well as lung damage, a reinfection with the same virus on day 28 post primary inoculation led to protection 89 .…”
Section: Discussionmentioning
confidence: 99%
“…In homologous reinfection experiments with ferrets, secondary challenge with SARS-CoV-2 Wuhan at day 28 or 56 post initial inoculation still maintained protection with no clinical signs reported or viral load detected 79,80 . Multiple studies have assessed infection-reinfection with the ancestral SARS-CoV-2 as well as variants revealing that while even heterologous reinfection with different variants decreases clinical signs and the presence of live virus, previous exposure to a SARS-CoV-2 virus does not lead to complete protection [81][82][83][84][85][86][87][88] . Hansen et al, assessed homologous reinfection with SARS-CoV-2 Wuhan, with the secondary challenge occurring at day 14, 49 and 152 days post primary and found that day 49 reinfection, the time point closest to our experimental design with a day 56 reinfection, was the most protective 85 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possession of both α2,6- and α2,3-linked sialic acid receptors means that hamsters are a suitable model for comparative studies between viruses with different sialic acid specificities, for example, human and avian viruses. Hamsters have been used extensively over the past three years in SARS-CoV-2 studies to assess the pathogenesis of emerging variants [ 32 , 33 , 34 ], the effect of countermeasures [ 35 , 36 , 37 ] and the impact of co-infection with influenza [ 38 ] or adenovirus [ 39 ].…”
Section: Discussionmentioning
confidence: 99%